Characterization of Leaf Essential Oil from Nutmeg (Myristica fragrans) Cultivated on Agroforestry Land - Hartari, Widia Rini; Hidayati, Sri; Utomo, Tanto Pratondo; Sartika, Dewi; Suharyono (Jurnal Sylva Lestari, 2024)
Lampung is the third largest producer of nutmeg (Myristica fragrans) in Sumatra Island, Indonesia. Most nutmeg essential oil refining industries in Lampung process nutmeg seeds, but not many distill nutmeg leaves. Therefore, it is necessary to identify the chemical compounds of nutmeg essential oil to determine the potential for further processing products and the quality of nutmeg essential oil. The leaf essential oil samples were obtained from a refining industry in Pesawaran, Lampung, Indonesia. The chemical compounds of the essential oils were identified using gas chromatography-mass spectrometry. Nutmeg leaf essential oil quality was then evaluated according to SNI 06-2388-2006 as standard testing for nutmeg oil. The data were then analyzed descriptively. The results identified 28 active compounds in nutmeg leaf essential oil. Compounds with high relative abundance were streptamine (76.46%), aquinolizine (4.67%), boron (3.73%), kaurene (2.03%), pyrrole (1.95%), and naphthalene. There were also terpenoid compounds that produced aromas, such as guaiol, borneol, cedrene, cubenol, and spathulenol. The quality assessment of leaf nutmeg essential oils also fulfilled the requirement of SNI 06-2388-2006. However, the optical produced rotation towards the left, namely -9.48°, and a specific gravity of 0.87, less than the SNI 06-2388-2006 requirement of 0.88. Nutmeg leaf essential oil has the potential to become a raw material for health and beauty products. Keywords: agroforestry, essential oil, nutmeg leaves, streptamine, terpenoid compounds